Design of 600 Wp Stand-alone Solar Tree Systemfor Public Charging Station - Handoko Rusiana Iskandar; Een Taryana; Bayu Ramdani; Muhammad Iqbal Naufal; Rifansyah Syaima Nasution; Thoriq Adzimar Ziyaulhaq (Fakultas Teknik Universitas Pancasila, 2025)
Indonesia has significant potential for solar energy utilization with a capacity of 313 MW. The solar tree system is an innovative alternative energy solution that combines functionality and aesthetics by utilizing limited space at Universitas Jenderal Achmad Yani as an electric charging station. The research methods include meteorological data, load calculations by operational time variations, component capacity analysis such as photovoltaic (PV) panels, batteries, inverters, and 3D modelling of the stand-alone Solar tree system. This paper discusses the analysis results for the most optimal operational time of 3 hours with a PV panel power requirement of 599.6 Wp, using 6 PV panels each rated at 100 Wp. The system is designed to supply daytime loads, including charging an electric bicycle 576 W and a laptop 65 W for three hours. At night, the battery supplies power for laptop charging and lighting with a total power of 317.5 Wh for twelve and a half hours. To ensure a two-day autonomy, a battery capacity of 12 V 80 Ah and a 1000 W inverter are considered in the design. The 3D solar tree system model is designed with a pole height of 4000 mm and a circular arrangement of 6 PV panels with a diameter of 4068 mm, equipped with table and chair facilities at several proposed locations, ensuring the Solar tree system design meets the desired capacity based on the selected scenario.